1999
DOI: 10.1111/j.1530-0277.1999.tb04099.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naltrexone on Alcohol Self‐Administration in Heavy Drinkers

Abstract: The mechanisms underlying the suppressant effects of naltrexone (NTX) on ad libitum alcohol drinking in a bar/restaurant setting were investigated in heavy beer drinkers. Fifty-one male and female heavy drinkers (mean age = 22) received 50 mg of NTX or placebo (PBO), p.o., on two separate occasions in a randomized, double-blind crossover protocol. After 7 days of taking medication, subjects were provided with the opportunity to consume beer ad libitum during two, 90-min test sessions that were held 1 to 2 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(76 citation statements)
references
References 20 publications
2
72
0
2
Order By: Relevance
“…Four different SA paradigms were represented, the most common (5 studies) being a paradigm involving administration of ‘mini‐drinks’ (target blood alcohol concentration increment .015 g/dl per drink), first published by O'Malley et al (2002). Other paradigms were reported by (Davidson et al ., 1996; 1999, Kruse et al ., 2012) and de Wit et al . (1999).…”
Section: Resultsmentioning
confidence: 99%
“…Four different SA paradigms were represented, the most common (5 studies) being a paradigm involving administration of ‘mini‐drinks’ (target blood alcohol concentration increment .015 g/dl per drink), first published by O'Malley et al (2002). Other paradigms were reported by (Davidson et al ., 1996; 1999, Kruse et al ., 2012) and de Wit et al . (1999).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to elicit a broad range of responses is a key feature of prior self-administration models (McKee et al, 2006; O’Malley, Krishnan-Sarin, Farren, Sinha, & Kreek, 2002), as such variability is necessary to observe effects of experimental manipulations or interventions on self-administration behavior in future studies. To enhance ecological validity, all self-administration sessions were conducted in an actual bar (Davidson, Swift, & Fritz, 1996; Davidson, Palfai, Bird, & Swift, 1999). Consistent with prior alcohol administration studies involving young adults (e.g., Corbin, Gearhardt, & Fromme, 2008; Sayette et al, 2012), sessions were conducted in groups of 2–4 participants to account for social factors that are critical to young adult drinking behavior (Sayette et al, 2012; Wood, Read, Palfai, & Stevenson, 2001).…”
mentioning
confidence: 99%
“…Booth et al (1992a) also reported alpha coefficients ranging from 0.52–0.85 for the 6 SPS subscales and an alpha of 0.86 for the Total score. The Positive and Negative Affect Schedule (PANAS; Watson, Clark, & Tellegen, 1988) was used by Davidson et al (Davidson, Palfai, Bird, & Swift, 1999) to assess positive mood in alcoholic patients. They found that positive mood was significantly lower when research participants were medicated with naltrexone as compared to placebo.…”
mentioning
confidence: 99%